2019
DOI: 10.1136/bmjopen-2019-030919
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of 13 immunosuppressive agents for idiopathic membranous nephropathy in adults with nephrotic syndrome: a systematic review and network meta-analysis

Abstract: ObjectivesThis study aimed to compare the effectiveness of 13 types of immunosuppressive agents used to treat idiopathic membranous nephropathy (IMN) in adults with nephrotic syndrome.DesignSystematic review and network meta-analysis.Data sourcesPubMed, EMbase, Cochrane Library, Web of Science, Clinical trials, SinoMed, Chinese Biomedicine, CNKI, WanFang and Chongqing VIP Information databases were comprehensively searched until February 2018.Eligibility criteriaRandomised clinical trials (RCTs) comparing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 55 publications
(104 reference statements)
2
18
1
1
Order By: Relevance
“…Our study differs from a previous network meta-analysis on idiopathic membranous nephropathy published in 2019, which compared 13 immunosuppressive agents against non-immunosuppressive therapy in 48 trials involving 2736 participants [76]. This study showed that most treatment strategies, except for leflunomide, mizoribine and steroid monotherapy, were significantly more likely to result in total remission compared with non-immunosuppressive therapies.…”
Section: Discussioncontrasting
confidence: 92%
“…Our study differs from a previous network meta-analysis on idiopathic membranous nephropathy published in 2019, which compared 13 immunosuppressive agents against non-immunosuppressive therapy in 48 trials involving 2736 participants [76]. This study showed that most treatment strategies, except for leflunomide, mizoribine and steroid monotherapy, were significantly more likely to result in total remission compared with non-immunosuppressive therapies.…”
Section: Discussioncontrasting
confidence: 92%
“…CY is used to treat a multitude of diseases, ranging from autoimmune disorders 28 , 29 to cancer to nonmalignant conditions treated with HCT. 9 , 14 With the increasing use of PT‐CY in alternative donor HCT, it is likely that CY use will expand.…”
Section: Discussionmentioning
confidence: 99%
“…Отчасти проблема конфаундинга в оценке эффективности лечения преодолена дополнительным межгрупповым сравнительным анализом с применением методов псевдорандомизации, который полностью подтвердил основные результаты исследования, повысив степень их надежности. Также нами не проведен анализ сравнительной эффективности нового подхода и стандартной терапии с применением ЦФ, что объясняется низкой частотой его применения в реальной практике клиники из-за высокого риска побочных эффектов и отмены лечения [6,22,23].…”
Section: Discussionunclassified